Peningkatan Kemampuan Kognitif Dalam Mengenal Angka 1-20 Melalui Permainan Jepit Hutan Pada Kelompok B Di TK Muslimat NU Bonang Demak - marini - marini; Yunita Ayu Anindi (Universitas Ivet, 2022)
The encouraging background in this research is early childhood education which is still low in cognitive learning, especially recognizing numbers 1-20 due to the lack of attractiveness of the learning methods used in learning activities. The aims of this study were (1) to improve children's cognitive abilities in recognizing numbers 1-20 in group B in TK Muslimat NU Sukodono through jungle flops game, (2) describe how to increase children's cognitive abilities in recognizing numbers 1-20 in group B in NU Muslimat Kindergarten in Sukodono through forest flops game. Then the CAR method is used as a way to reduce existing problems. The results of this study indicate that jungle flops game can increase cognitive abilities in recognizing numbers. These results can be seen after the CAR process is carried out starting from the pre-cycle process, cycle I to cycle II. In the implementation of two cycles, there was a significant increase in the child's ability to recognize numbers. The results of the study was children's ability in recognizing numbers 1-20 was increased to 13,33 % in the first cycle and increased to 80% in cycle II. Based on the results, this study concluded that the children's ability in recognizing number 1-20 can be increased by playing forest flops.